2007
DOI: 10.1111/j.1572-0241.2006.01109.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection and the Risk of Gastric Malignancy

Abstract: In this prospective cohort study, all gastric malignancies, including adenocarcinoma and lymphoma, developed in H. pylori-infected patients. The finding implies that H. pylori is a necessary cause of most gastric malignancies. Follow-up for H. pylori-infected patients who have intestinal metaplasia is indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 22 publications
1
70
0
10
Order By: Relevance
“…The frequency of H pylori infection (94.4%) was higher than previous studies, where it ranged from 34.1% to 92%. These differences can be due to: (a) the sensitivity of the screening technique, since most previous studies used serology, rapid urease test and/or histological evaluation; (b) and the fact that these studies were performed in different world regions and it is known that the H pylori infection is more frequent in developing countries [8,16,[22][23][24] . On the other hand, EBV was detected in 8.45% of our cases.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of H pylori infection (94.4%) was higher than previous studies, where it ranged from 34.1% to 92%. These differences can be due to: (a) the sensitivity of the screening technique, since most previous studies used serology, rapid urease test and/or histological evaluation; (b) and the fact that these studies were performed in different world regions and it is known that the H pylori infection is more frequent in developing countries [8,16,[22][23][24] . On the other hand, EBV was detected in 8.45% of our cases.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many other inflammatory triggers are associated with other malignancies, including microbial infection, such as Helicobacter pylori infection, associated with gastric cancer, autoimmune responses associated with inflammatory bowel disease and colorectal cancer and sexualtransmitted infections with prostatitis and prostate cancer [65][66][67].…”
Section: Cancer and Ageingmentioning
confidence: 99%
“…Similarly, in a small cohort study, in which H. pylori status was ascertained by histological examination, rapid urease test, and serologic test, 3% of infected subjects but none of the uninfected developed a stomach cancer, after a mean followup time of 7.8 years [25]. Another study conducted in Taiwan with a similar study design also reported none of stomach malignancies detected among the uninfected subjects after a mean follow-up of 6.3 years [26].…”
Section: Discussionmentioning
confidence: 78%